Основи соціальної роботи з неблагополучною сім’єю ( з досвіду викладання навчальної дисципліни «соціальна робота з сім’єю») - Бичук, Ірина (My University, 2018)
У статті подається конспективний виклад лекції «Основи соціальної роботи з неблагополучною сім’єю» в контексті обміну досвідом викладання навчальної дисципліни «Соціальна робота з сім’єю» у вищих навчальних закладах України. Соціальна робота з сім’єю є системою взаємодії соціальних органів держави і суспільства та сім’ї. Соціальна робота з сім’єю спрямована на поліпшення матеріальних та побутових умов життя сім’ї, забезпечення повноцінного фізичного, морального й духовного розвитку усіх членів сім’ї. Основна мета соціальної роботи з сім’єю – це соціальна профілактика, соціальна допомога, соціальний патронаж, соціальна реабілітація, надання їй соціально-психологічної, психолого-педагогічної, соціально-медичної, юридичної, інформативно-консультативної, психотерапевтичної допомоги.The article gives a concise presentation of the lecture "Fundamentals of social work with a dysfunctional family" in the context of the exchange of experience in teaching the subject "Social work with the family" in higher educational institutions of Ukraine. Social work with the family is a system of interaction between social bodies of the state and society and family. Social work with the family is aimed at improving the material and living conditions of the family, ensuring the full physical, moral and spiritual development of all family members. The main purpose of social work with the family is social prophylaxis, social assistance, social patronage, social rehabilitation, providing it with socio-psychological, psychological and pedagogical, social-medical, legal, informative-consultative, psychotherapeutic assistance. Disadvantaged families are families who, because of objective or subjective reasons, have lost their educational opportunities, as a result of which they have unfavorable conditions for the upbringing of the child. It has been characterized that social work with a dysfunctional family is aimed at creating conditions for overcoming her causes and consequences of her distress. The task of a specialist in working with a dysfunctional family is analyzed. The main stages of social and pedagogical support of a dysfunctional family are described. The basic technologies of social work with disadvantaged families are revealed: social support and social counseling.
Keywords: соціальна робота; social work; соціальний працівник; неблагополучна сім’я; соціально - педагогічний супровід; соціальна опіка; соціальний патронаж; сімейне консультування; social worker; dysfunctional family; social and pedagogical support; social care; social patronage; family counseling